Bio-energy, Productivity and Economics of rice (Oryza sativa L.)-based Cropping Systems in Coastal Flood Plain of West Bengal, India - Roy, D. C.; Ray, M.; Sarkar, U.; Patra, B. C. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was carried out at farmers’ field in coastal saline zone of West Bengal, India during 2011-12 and 2012-13 with four cropping systems viz. rice-greengram, rice-sunflower, rice-sunflower+greengram and rice-lady’s finger. Rice-lady’s finger system recorded significantly higher rice equivalent yield, system productivity in both the years. Significantly higher net return (` 1,05,670 ha-1) was obtained in rice-lady’s finger cropping system, followed by rice greengram, whereas B:C ratio was found at par. Among the management components fertilizer consumed maximum energy followed by operational labour and land preparation. Energy consumption was found significantly higher in rice-lady’s finger system (44,902 MJ ha-1) and lowest in rice-greengram system (29,005 MJ ha-1). Total bioenergy output follows the order: rice-lady’s finger>rice-sunflower>rice-sunflower+greengram>rice-greengram. But this order was reversed for energy-use efficiency (EUE). Significantly higher specific energy was recorded in rice-sunflower system (3415 MJ t-1) and it was the most energy-investment intensive among them. However, significantly higher energy productivity was observed in rice-lady’s finger system (0.63 kg MJ-1) and lowest in rice-greengram (0.30 kg MJ-1). Regarding energy intensiveness the results were contrary to EUE. Rice-lady’s finger system was emerged as most energy intensive system as compared to other three cropping systems and the rice-greengram system is the least. It can be concluded that though the yield and net return in rice-lady’s finger system were higher than other system, the rice-greengram system is more suitable cropping system in constrains prone coastal saline zone with limited irrigation facilities due to low requirement of non-renewable energy, higher EUE and benefit-cost ratio.